Balancing new technology: Virtual reality for balance measurement case report. Issue 5 (3rd February 2023) - Weissberger, Omer; Orr, Eran; Levy, Miki; Kimel-Naor, Shani; Plotnik, Meir; Arbel, Tal
Abstract : Rationale: Falling and the inability to maintain balance are the second leading cause of unintentional injury deaths globally. There are a number of chronic and acute conditions characterized by balance difficulties, including neurological diseases, and sport injuries. Therefore, methods to monitor and quantify balance are critical for clinical decision-making regarding risk management and balance rehabilitation. New advances in virtual reality (VR) technology has identified VR as a novel therapeutic platform. VRSway is a VR application that uses sensors attached to a virtual reality headset, and handheld remote controllers for measurement and analysis of postural stability by measuring changes in spatial location relative to the center of mass and calculates various postural stability indexes. This case report evaluates balance measures in 2 healthy participants with no previous history of balance disorders using the VRSway software application and compares to output generated by the current gold standard of balance measurement, force platform technology. Case Presentation: The primary objective of this case study was to validate the VRSway stability score for evaluation of balance. Here, we present posturography measures of the VRSway in comparison with force plate readouts in 2 healthy participants. Body Sway measurements were recorded simultaneously in both the force plate and VRSway systems. Data calculated by proprietary software is highly correlative to the data generated by force plates for each of the following measurements for participant-1 and participant-2, respectively: Sway index (r 1 = 0.985, P < .001; r 2 = 0.970, P < .001), total displacement (r 1 = 0.982, P < .001; r 2 = 0.935, P < .001), center of pressure mean velocity (r 1 = 0.982, P < .001; r 2 = 0.935, P < .001), ellipse radius 1 (r 1 = 0.979, P < .001; r 2 = 0.965, P < .001), ellipse radius 2 (r 1 = 0.982, P < .001; r 2 = 0.969, P < .001), and ellipse area (r 1 = 0.983, P < .001; r 2 = 0.969, P < .001). Conclusions: Data from this case study suggest that VRSway measurements are highly correlated with output from force plate technology posing that VRSway is a novel approach to evaluate balance measures with VR. More research is required to understand possible uses of VR-based use for balance measurement in a larger and more diverse cohort.